Siri’ Based Internal Quality Assurance - Arhas, Sitti Hardiyanti; Arismunandar, Arismunandar; Saleh, Sirajuddin; Ardiansyah, Muhammad (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2025)
Internal quality assurance is a strategic element in maintaining the quality and credibility of education delivery. However, the implementation still tends to be administratively oriented and has not fully touched the dimensions of academic values and integrity. This study aims to analyze the development of scientific studies on internal quality assurance and examine the relevance of Siri’ values as an ethical foundation in strengthening academic integrity. This study uses a quantitative approach with a bibliometric analysis method. Data was obtained from Scopus indexed scientific publications relevant to the topics of internal quality assurance and academic integrity, then analyzed using the VOSviewer software through keyword co-occurrence techniques. The results of the study show that internal quality assurance has a strong relationship with academic integrity, self-evaluation, quality implementation competence, and the role of external quality assurance. These findings confirm that integrity is a key prerequisite for the effectiveness of internal quality assurance. The value of Siri’ as local wisdom is seen as relevant to strengthen the dimensions of moral awareness, academic responsibility, and institutional honor in the implementation of quality assurance. This research contributes to the development of conceptual understanding of internal quality assurance based on local cultural values as an effort to build a sustainable culture of educational quality.